2021
DOI: 10.1029/2021gl092719
|View full text |Cite
|
Sign up to set email alerts
|

Future Evolution of an Eddy Rich Ocean Associated with Enhanced East Atlantic Storminess in a Coupled Model Projection

Abstract: Improved representation of air‐sea fluxes afforded by eddy‐rich oceans in high‐resolution coupled ocean‐atmosphere models may modify the tracks and intensity of storms and their response to climate change. We examine changes in winter surface ocean conditions and storminess associated with moving from an eddy‐permitting (1/4°, HM) to an eddy‐rich (1/12°, HH) ocean in control and climate change (SSP585) simulations of the HadGEM3‐GC3.1 model in which atmosphere resolution is kept at 25 km. Differences in North … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…In the face of limited computing resources and a demand for finer resolutions in ocean modelling, it is advantageous to reduce net computational effort relative to grid resolution. Existing modelling studies of ocean eddies tend to rely on idealized simulations 10 , ocean-only models 25,26 or simulations limited in spatial coverage, ensemble size or length 15,[27][28][29] . In contrast, the Finite Element Sea-ice Ocean Model 30,31 (FESOM) enables the concentration of computational resources via an unstructured mesh with which the spatial resolution of regions can be adjusted based on relevance to the global climate system and the needs of the user [31][32][33] .…”
Section: Model Performance and Contextualization Of Observationsmentioning
confidence: 99%
“…In the face of limited computing resources and a demand for finer resolutions in ocean modelling, it is advantageous to reduce net computational effort relative to grid resolution. Existing modelling studies of ocean eddies tend to rely on idealized simulations 10 , ocean-only models 25,26 or simulations limited in spatial coverage, ensemble size or length 15,[27][28][29] . In contrast, the Finite Element Sea-ice Ocean Model 30,31 (FESOM) enables the concentration of computational resources via an unstructured mesh with which the spatial resolution of regions can be adjusted based on relevance to the global climate system and the needs of the user [31][32][33] .…”
Section: Model Performance and Contextualization Of Observationsmentioning
confidence: 99%
“…Note, the projections follow the SSP585 future scenario, for full details see Grist et al . [ 23 ]. The figure shows greater warming with the high-resolution ocean particularly at about 45°S, which is north of the Subantarctic Front.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies such as Bengtsson et al (2009) and Booth et al (2018) found improved representation of cyclones with higher resolution, and the HighResMIP models have been noted to have considerable benefits compared to standard resolution CMIP6 models in terms of explosive ETC wind speed and tropical cyclone intensity (Jiaxiang et al, 2020;Roberts et al, 2020), which we add further evidence to in this study, with the models offering improvements over their lower resolution counterparts. Improved resolution has also shown to be important in future projections, with higher resolution models projecting greater storminess in the North Atlantic by the end of the century (Grist et al, 2021). Therefore, a key research directive should be to assess what processes associated with higher resolution are driving the improvements in HighResMIP models.…”
Section: Discussionmentioning
confidence: 99%